Meningkatkan Hasil Belajar Melalui Model Problem Based Learning Pada PAK Kelas IV SD Negeri 20 Saibi Samukop, TP 2023/2024. - Asal Murni Zendrato (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
. At school, Catholic Religious Education (PAK) is one of the religious subjects expected to develop students' critical, logical, and systematic thinking abilities and demonstrate their objective, neutral nature. Be realistic and disciplined in solving everyday problems. However, in school, teachers tend to consider transmitting information as the most important activity in learning activities. This situation becomes problematic when in learning, students must actively participate and interact with the environment. However, for this reason, the realities that researchers experience in class are among the factors that influence students' low learning ability, including: The learning process is too theoretical theory and memorization in all subjects, therefore, Students are less interested or motivated to learn because they feel bored, lazy and the impact of this on these students is that they are poor. Be proactive and creative in developing thinking skills and skills to overcome problems encountered, thereby affecting the learning atmosphere. Is passive and includes students' own reasoning, they will be less successful in their studies. Independent curriculum learning uses problem-based learning, this learning model is an alternative solution to improve student learning outcomes in PAK subjects. Problem-based learning (PBL) is an educational method that uses real-world problems as a context to help students learn to think critically and develop problem-solving skills, as well as acquire essential skills and concepts of the subject